In Vivo engineering of transgenic mice for systemic human neutralizing antibody production against staphylococcal enterotoxin B - Jiang, Zhiyang; Jia, Beichen; Hu, Naijing; Zhang, Mengmeng; Xiao, He; Chen, Guojiang; Yu, Jijun; Li, Xinying; Shen, Beifen; Feng, Jiannan; Wang, Jing (Frontiers in Immunology, 2025)
Transgenic animal bioreactors provide a complementary strategy to traditional mammalian cell culture systems for the production of therapeutic human monoclonal antibodies (mAbs). Here we present a CRISPR/Cas9-mediated breakthrough in creating two novel genetically engineered (GE) mouse models with species-specific chromosomal integration of human anti-staphylococcal enterotoxin B (SEB) mAb genes at either the ROSA26 or Hipp11 (H11) safe-harbor loci - evolutionarily conserved genomic safe harbors (GSH). These genetically optimized animals demonstrated broad tissue capability for glycosylation-competent human antibodies, achieving exceptional secretion levels reaching 208 mg/L in serum, 43 mg/L in mammary secretions, 24 mg/L in saliva on average. The transgenic lines maintained this antibody production stability for >140 weeks without compromising animal viability, while preserving germline transmission fidelity through six successive generations. Furthermore, the highly glycosylated human antibodies derived from these genetic engineered mice exhibited high binding affinity to SEB (KD=0.108 nM for ROSA26; 0.154 nM for H11), providing comprehensive protection against SEB intoxication in vivo. This study opens avenues for utilizing transgenic animal bioreactors for large-scale production of fully human antibodies or disease-resistant livestock in the foreseeable future.